Design of a Secure Medical Data Sharing Scheme Based on Blockchain. - Cheng, Xu; Chen, Fulong; Xie, Dong; Sun, Hui; Huang, Cheng (Journal of Medical Systems, 2020)
With the rapid development of technologies such as artificial intelligence, blockchain, cloud computing, and big data, Medical Cyber Physical Systems (MCPS) are increasingly demanding data security, while cloud storage solves the storage problem of complex medical data. However, it is difficult to realize data security sharing. The decentralization feature of blockchain is helpful to solve the problem that the secure authentication process is highly dependent on the trusted third party and implement data security transmission. In this paper, the blockchain technology is used to describe the security requirements in authentication process, and a network model of MCPS based on blockchain is proposed. Through analysis of medical data storage architecture, it can ensure that data can't be tampered and untrackable. In the security authentication phase, bilinear mapping and intractable problems can be used to solve the security threat in the authentication process of medical data providers and users. It can avoid the credibility problem of the trusted third party, and also can realize the ?thyc=10?>two-way authentication between the hospital and blockchain node. Then, BAN logic is used to analyze security protocols, and formal analysis and comparison of security protocols are also made. The results show that the MCPS based on blockchain not only realizes medical treatment data sharing, but also meet the various security requirements in the security authentication phase. In addition, the storage and computing overhead costs is ideal. Therefore, the proposed scheme is more suitable for secure sharing of medical big data.